The Role of the Binmas Unit through Counseling in Preventing Theft in the Jayapura Police's Legal Area - Franciscus Lamalouk (Police Studies Review, 2021)
In order to prevent this, the Binmas Unit takes preventive and remedial steps to prevent the occurrence of this theft from increasing, the Jayapura Police prioritizes the role of the Binmas Unit which directs Bhabinkamtibmas in the ranks of the Polsek in its implementation. In this research, the author aims to find out about what efforts have been carried out by the Jayapura Police Binmas Unit in counseling to prevent the case of theft, then what factors affect the task of the Jayapura Police Binmas Unit in preventing the crime of motor vehicle theft in Indonesia. the jurisdiction of the Jayapura Police. Implementation of this research the author uses a qualitative approach and field research methods. Where in the process of collecting data the author carried out several activities, namely by means of observation, interviews, and reviewing documents. The data was processed using descriptive analysis. As an analytical tool for all existing data, the author uses several theories and concepts, namely management theory, role theory, Binmas Unit Concept and Extension Concept. Based on the results of research that has been carried out by the community who appreciates the performance of the Binmas Unit from the Jayapura Police in carrying out their responsibilities, this appreciation from the community is given to the Binmas Unit because the officers have carried out their duties in accordance with the applicable regulations, namely Perkap Number 21 of 2007 concerning Binluh , in which the Perkap discusses the tasks carried out by the Binmas Unit. In its daily implementation, there are factors that support and hinder the role of the Binmas Unit. The supporting factor is the role of the National Police who help each other between the government and the city community and for the inhibiting factor is the inadequate facilities and infrastructure and the lack of concern from the community for the members of this Binmas Unit, especially in several sub-districts that are far from the city. As a suggestion for the leadership of the Jayapura Police, namely to provide various facilities and infrastructure and provide interesting innovations so that the community is more comfortable, which is also needed by members of the Binmas Unit.